Limitations in Countering Armed Group Conflicts, Tactics and Vulnerable Targets in Nigeria - Adeyeye, Adebowale Idowu (Kashere Journal of Politics and International Relations, 2024)
The activities and the negative consequences of armed groups in Nigeria have been one fundamental crisis facing the country over the past decade. This paper is solicitous of the limitations in tackling armed group conflicts and the vulnerable targets. Using content analytical methods of data gathered from secondary sources, it examines armed groups activities and the country’s counterinsurgency and counterterrorism operations. The paper argues that though these groups does not have overwhelming firepower or numbers than the state forces but the fundamental constraints in fighting armed groups are in how the military forces can tackle their irregular and unconventional tactics, the challenges of maintaining public supports in the operating environments’ (OE) and the problem of harming the vulnerable targets. It further contends that state cohesiveness, the role of ideology and information technology, duration of conflict and the influences of external actors, also contribute to the constraints not only in traditional warfare but in countering armed group conflicts in Nigeria. It concludes that the traditional constraints in warfare tactics are eroded in the armed conflict warfare in the country arising from above stated limitations as such must be adequately considered in the counterinsurgency and counterterrorism operations.